Menelusuri Kata ‘‘Wabah‘‘ dan ‘‘Tho’un‘‘ dalam Korpora Diakronis Arab-Indonesia - Kamal Yusuf (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2020)
This study tries to trace the meaning of wabah and tho‘un as they are used in Arabic and Indonesian language. To do so, three diachronic corpora were utilized as resources. They are Malay Concordance Project corpora (MCP), Leipzig Corpora collection, and WebCorp. MCP was used to determine the word wabah and tho’un in pre-modern era. Leipzig corpora was used to demonstrate the collocation and concordance of the studied words. WebCorp was used to trace their used in the modern era and in more recent texts. This study revealed that wabah is originally from وباء, a word that is borrowed from Arabic waba‘. The used of wabak was found in 1500’s, in pre-modern texts. This word furthermore becomes wabah in modern uses. Unlike, the words tho‘un (read: ṭāʻūn) was unknow in the pre-modern era. In modern era, the word wabah and tho‘un are used in context related to health, not far from their original meaning. The findings of this study furthermore, pave the way for the importance use of corpus for the development of Indonesian words etymology and its lexicography.